2006
DOI: 10.1158/1078-0432.ccr-05-2556
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator–Activated Receptor α Activation Decreases Metastatic Potential of Melanoma Cells In vitro via Down-Regulation of Akt

Abstract: Purpose: Peroxisome proliferator-activated receptors (PPAR) regulate lipid and glucose metabolism but their anticancer properties have been recently studied as well.We previously reported the antimetastatic activity of the PPARa ligand, fenofibrate, against melanoma tumors in vivo.Here we investigated possible molecular mechanisms of fenofibrate anti metastatic action. Experimental Design: Monolayer cultures of mouse (B16F10) and human (SkMell88) melanoma cell lines, soft agar assay, and cell migration assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
149
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 51 publications
8
149
0
Order By: Relevance
“…They may be used for maintenance of long-term angiogenesis suppression. Furthermore, our findings support recent studies (11)(12)(13)(14) that suggest that PPAR␣ ligands may be ideally suited to complement conventional modalities for cancer treatment. Specifically, because fenofilerate is commercially available, it could be evaluated as an extension of existing multidrug regimens, notably in metronomic (antiangiogenic) chemotherapy schemes (38,39).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They may be used for maintenance of long-term angiogenesis suppression. Furthermore, our findings support recent studies (11)(12)(13)(14) that suggest that PPAR␣ ligands may be ideally suited to complement conventional modalities for cancer treatment. Specifically, because fenofilerate is commercially available, it could be evaluated as an extension of existing multidrug regimens, notably in metronomic (antiangiogenic) chemotherapy schemes (38,39).…”
Section: Discussionsupporting
confidence: 89%
“…However, recent studies have revealed the expression of PPAR␣ in tumor cells (5, 6), and PPAR␣ ligands suppress the growth of several cancer lines, including colon, breast, endometrial and skin, in vitro (7-10). PPAR␣ ligands also suppress the metastatic potential of melanoma cells in vitro and in vivo (11,12). Furthermore, PPAR␣ ligands decrease tumor development in murine colon carcinogenesis (7).…”
mentioning
confidence: 99%
“…Time-lapse experiments revealed that fenofibrate inhibited 'contactstimulated' motility of DU-145 cells. An inhibitory effect of fenofibrate on the invasiveness of melanoma (12,13) and glioblastoma cell migration (18) has previously been demonstrated. These experiments, however, did not address the problem of 'contact-stimulated' cell motility and, moreover, described PPARα-dependent cell responses to fenofibrate.…”
Section: Discussionmentioning
confidence: 89%
“…Among them, fenofibrate is commonly used in the prevention of arteriosclerosis as a lipid-lowering drug (9). It is of interest that fibrates in general exert a wide range of anti-cancer properties (10)(11)(12)(13)(14). In particular, fenofibrate was shown to interfere with the growth and survival of different cancer cell types in a manner dependent on the activation of peroxisome-proliferator activated receptor-α (PPARα) (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation